2023
DOI: 10.3389/fsurg.2022.807467
|View full text |Cite
|
Sign up to set email alerts
|

A novel predictive model of hospital stay for Total Knee Arthroplasty patients

Abstract: ObjectiveThis study aimed to explore the main risk factors affecting Total Knee Arthroplasty (TKA) patients and develop a predictive nomogram of hospital stay.MethodsIn total, 2,622 patients undergoing TKA in Singapore were included in this retrospective cohort study. Hospital extension was defined based on the 75% quartile (Q3) of hospital stay. We randomly divided all patients into two groups using a 7:3 ratio of training and validation groups. We performed univariate analyses of the training group, in which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
1
0
0
Order By: Relevance
“…[28][29][30] Nomogram has been widely studied in predicting clinical outcomes after orthopedic surgery. [31][32][33] The nomogram prediction model constructed based on the identified risk factors in the current study also showed a good prediction performance, which is consistent with the findings by Liu et al 10 The score of our nomogram model may be used to calculate the risk of postoperative chronic pain. The specified indicators are easy to obtain in clinical practice, which allows to perform early intervention.…”
Section: Discussionsupporting
confidence: 90%
“…[28][29][30] Nomogram has been widely studied in predicting clinical outcomes after orthopedic surgery. [31][32][33] The nomogram prediction model constructed based on the identified risk factors in the current study also showed a good prediction performance, which is consistent with the findings by Liu et al 10 The score of our nomogram model may be used to calculate the risk of postoperative chronic pain. The specified indicators are easy to obtain in clinical practice, which allows to perform early intervention.…”
Section: Discussionsupporting
confidence: 90%